2016
DOI: 10.1007/7651_2016_330
|View full text |Cite
|
Sign up to set email alerts
|

Detection of C-Peptide in Urine as a Measure of Ongoing Beta Cell Function

Abstract: SUMMARYC-peptide is a protein secreted by the pancreatic beta cells in equimolar quantities with insulin, following the cleavage of proinsulin into insulin. Measurement of C-peptide is used as a surrogate marker of endogenous insulin secretory capacity. Assessing C-peptide levels can be useful in classifying the sub-type of diabetes as well as assessing potential treatment choices in the management of diabetes.Standard measures of C-peptide involve blood samples collected either fasted or, most often, after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have shown that UCPCR is a useful alternative to blood CP and 24-h UCP tests, and can better reflect the function of the islet. Other tests have some limitations such as the instability of blood CP and the difficulty in 24-h UCP sample retention, but UCPCR sample can be stored for at least 3 days at room temperature with the addition of boric acid preservative ( 21 ). The experiment adopted in this paper has little interference from proteinuria and naked eye hematuria, and has stable performance and high stability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that UCPCR is a useful alternative to blood CP and 24-h UCP tests, and can better reflect the function of the islet. Other tests have some limitations such as the instability of blood CP and the difficulty in 24-h UCP sample retention, but UCPCR sample can be stored for at least 3 days at room temperature with the addition of boric acid preservative ( 21 ). The experiment adopted in this paper has little interference from proteinuria and naked eye hematuria, and has stable performance and high stability.…”
Section: Discussionmentioning
confidence: 99%
“…Urine C-peptide measurement is a less invasive and practical alternative to serum C-peptide measurements (5). Furthermore, Urinary C-peptide to creatinine ratio (UCPCR) is a surrogate marker for endogenous insulin secretion (7).…”
Section: Introduction Backgroundmentioning
confidence: 99%